DEWBoard and EDUNEXA win CITREX 2025 Best of the Best Awards - Naqiah, Puaad (UMPSA, 2025)
GAMBANG, 19 June 2025 – A project titled ‘DEWBoard’ by a lecturer from the Faculty of Electrical and Electronic Engineering Technology (FTKEE), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), Nurul Wahidah Arshad, won the Best of the Best Award in the staff category at the 15th Creation, Innovation, Technology & Research Exposition (CITREX) 2025.